2008
DOI: 10.1038/clpt.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamic Effects of Oral GLP-1 and PYY3-36: A Proof-of-concept Study in Healthy Subjects

Abstract: This proof-of-concept study was performed in order to establish the pharmacokinetics and pharmacodynamics of increasing oral doses of the satiety peptides glucagon-like peptide-1 (GLP-1) and peptide YY3-36 (PYY3-36). Six healthy male subjects were given oral doses of either a placebo or GLP-1 in a dose-escalating schedule (doses of 0.5, 1.0, 2.0, and 4.0 mg). Next, another group of six healthy male subjects were given oral doses of either a placebo or PYY3-36 in the same pattern of escalating doses (doses of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 30 publications
(37 reference statements)
1
34
0
Order By: Relevance
“…It was isolated originally from porcine intestinal and it is able to cross the blood brain barrier through a non-saturable mechanism (20,21). The effects of PYY3-36 on food intake have been investigated in several animal species and also in humans (22,23). In rodents, it has been shown that PYY administration can reduce both food intake and body weight (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was isolated originally from porcine intestinal and it is able to cross the blood brain barrier through a non-saturable mechanism (20,21). The effects of PYY3-36 on food intake have been investigated in several animal species and also in humans (22,23). In rodents, it has been shown that PYY administration can reduce both food intake and body weight (24).…”
Section: Introductionmentioning
confidence: 99%
“…A longer lasting clinical trial has also been conducted by Nastech Pharmaceutical Company Inc. (34) using intranasal PYY3-36 with a similar administration frequency as in the previous study. Recently, PYY3-36 has been combined with GLP-1 and the combination was administered orally with a delivery agent SNAC, but elevated plasma concentrations could only be detected for 2 h (23). Since all of these tested delivery systems require repeated administration, a sustained release system would be preferable.…”
Section: Introductionmentioning
confidence: 99%
“…5 Prolonged reductions in both plasma glucose and ghrelin levels were observed, indicating a multifaceted means of controlling food intake. These long-lasting effects stimulated by transient GLP-1 presence are suggestive of stimulation of portal neuronal signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For oral application of GLP-1, the Eligen technology is being investigated (Beglinger et al, 2008). Eligen is a drug delivery agent forming a conformational complex with the peptide that is protected against degradation and helps the peptide to be absorbed.…”
Section: Reduction Of Rapid Renalmentioning
confidence: 99%